Determining of passenger load factor for public bus transportation in Northern Peninsular Malaysia - Norhisham, Shuhairy; Mohd Azlan, Nor Najwa Irina; Abu Bakar, Muhammad Fadhlullah; Mohd Saad, Noorazizun; Wan Mohd Fauzi,, Wan Ahmad Faiz; Masjuki, Siti Aliyyah; Ramli, Mohd Zakwan; Samsudin, Sarah Shaziah (Springer, Cham, 2022)
Over the decade, Malaysia showed excellent improvement in upgrading social mobility as the country moving to become a developing nation. The important factor of social mobility that needs to be highlighted is transportation. Day-to-day activities require transportation to move from one place to another. Having systematic and reliable public transportation ensures the well-being and satisfaction of users. This paper proposes to determine the passenger load factor specifically for public bus transportation in Northern Peninsular Malaysia. The number of passengers and the number of seats in a bus is needed to rate the passenger load factor according to their Quality of Service (QOS) from Transit Capacity and Quality Service Manual (TCQSM) 3rd Edition. The results of passenger load factor for Kangar, Alor Setar, Georgetown, and Ipoh in Northern Peninsular Malaysia were found to be at 0.07, 0.23, 0.56, and 0.14 respectively. The capital cities investigated in this study are rated as A for their QOS except for Georgetown at B. Although the QOS rated as excellent, some aspects need to be improvised such as better on-time performance and longer duration of service hours to encourage more users of public bus transportation and eventually increase the passenger load factor.